Phenotypic and Genotypic Isolation of MRSA from Burn Wound Infected Patients at a Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Infectious Diseases, 2020)
Background: Patients of burn wound are generally more susceptible to infection due to concurrent status of malnutrition and immunosuppression. Among many bacteria, MRSA has appeared as a challenging pathogen irrespective of effective antibiotic therapy.Objective: The purpose of the present study was to detect the prevalence and antibiogram of MRSA in burn wound infected patients.Methodology: The present cross sectional study was conducted at Department of Microbiology in Rajshahi Medical College, Rajshahi, Bangladesh. The samples were collected from Burn and Plastic Surgery Unit of Rajshahi Medical College Hospital, for a period of one year. Phenotypic detection of MRSA were done by cefoxitin disc diffusion method and genotype (mecA gene) was detected by PCR which was conducted at Dhaka Medical College, Dhaka among all the S. aureus isolates.Result: A total of 212 wound swabs were subjected to bacteriological culture media for isolation of MRSA and other organisms. As a whole 89.62% samples yielded growth in culture of which Pseudomonas aeruginosa was the predominant pathogen (34.18%). Out of 21 S.aureus isolates, 07(33.33%) were detected as MRSA by cefoxitin resistance and presence of mecA gene. Although over 85% MRSA were resistance to ciprofloxacin and ceftriaxone, but the present study could not detect any vancomycin resistant MRSA.Conclusion: The high prevalence and decreased sensitivity of MRSA to commonly used antibiotics has been observed in Burn Unit of RMCH. Therefore it is necessary to establish an antimicrobial surveillance system in hospital settings to prevent the spread of MRSA.Bangladesh Journal of Infectious Diseases 2020;7(1):12-17